The geomicrobiology of CO2 geosequestration: a focused review on prokaryotic community responses to field-scale CO2 injection - Mu, Andre; Moreau, John W. (Frontiers in Microbiology, 2015)
Our primary research paper, titled Changes in the deep subsurface microbial biosphere resulting from a field-scale CO2 geosequestration experiment (Mu et al., 2014), demonstrated selective changes to a deep subsurface prokaryotic community as a result of CO2 stress. Analysing geochemical and microbial 16S rRNA gene profiles, we evaluated how in situ prokaryotic communities responded to increased CO2 and the presence of trace organic compounds, and related temporal shifts in phylogeny to changes in metabolic potential. In this focused review, we extend upon our previous discussion to present analysis of taxonomic unit co-occurrence profiles from the same field experiment, to attempt to describe dynamic community behaviour within the deep subsurface. Understanding the physiology of the subsurface microbial biosphere, including how key functional groups integrate into the community, will be critical to determining the fate of injected CO2. For example, community-wide network analyses may provide insights to whether microbes cooperatively produce biofilm biomass, and/or biomineralise the CO2, and hence, induce changes to formation porosity or changes in electron flow. Furthermore, we discuss potential impacts to the feasibility of subsurface CO2 storage of selectively enriching for particular metabolic functions (e.g., methanogenesis) as a result of CO2 injection.